Organizational culture: unveiling intersubjective meanings in an autonomous Venezuelan university - Verenzuela-Barroeta, Daniel Antonio; Salas-Hernández, Adrian (Estudios de Administración, 2021)
The purpose of the research is to reveal, understand and interpret the meanings that university managers attribute to the organizational culture of the Faculty of Economic and Social Sciences of the University of Carabobo, from the interpretive paradigm under the qualitative approach; the epistemic approach adopted the experiential vivencialism while the methodology followed the hermeneutical phenomenological method. As sample, five university managers were intentionally selected, whose interpretations were diagnosed through in-depth interviews. Recording, categorization and coding protocols were applied to the information collected and three natural categories emerged: cultural production, philosophical ethos and cultural ontology. These concepts were interpreted and contrasted with state-of-the-art cultural analysis as proposed by Schein (1988). Cultural production represents the peripheral level of culture, values are an instrumental means that is articulated with previous learning to configure identity, and cultural genesis is rooted in the philosophical ethos, hence actions are mediated by the synergy of the two former levels. University management and the Venezuelan socioeconomic situation have weakened the hitherto shared understanding of the organizational culture.